Hubungan Pengetahuan Gizi Seimbang dengan Status Gizi Calon Pengantin di Wilayah Kerja UPTD Puskesmas Kemalaraja OKU - Della Tiara; Andicha Gustra Jeki; Iin Indrawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
The nutritional health status of the prospective bride is a reflection of the physical well-being of the prospective bride due to the fulfillment of nutritional needs in the body. The prospective bride's nutrition can influence reproductive health to prepare for reproduction from preconception, pregnancy, childbirth and postpartum. Knowledge about nutrition plays an important role in fulfilling a person's nutritional adequacy. The aim of this research was to determine the relationship between knowledge of balanced nutrition and the nutritional status of prospective brides and grooms at the Kemalaraja OKU Community Health Center UPTD. This type of research is descriptive research with a cross sectional approach carried out in June - July 2024. The sample size of 17 female catins was determined using a total sampling technique. Data analysis in this study used univariate and bivariate analysis using the chi-square test to determine the relationship between nutritional knowledge and the nutritional status of prospective brides and grooms at the Kemalaraja OKU Health Center UPTD. The results of univariate analysis showed that the average age range was 24-28 years (47.1%), good nutritional knowledge (64.7%), normal nutritional status (70.6%). There is a relationship between knowledge of balanced nutrition and catin nutritional status (p = 0.000). From this research, it can be concluded that there is a relationship between knowledge of balanced nutrition and catin nutritional status in the working area of ​​the Kemalaraja OKU Public Health Center UPTD. It is recommended that prospective brides and grooms increase their nutritional knowledge by looking for information about balanced nutrition.